Total Coumarins from Hydrangea paniculata Show Renal Protective Effects in Lipopolysaccharide-Induced Acute Kidney Injury via Anti-inflammatory and Antioxidant Activities - Zhang, Sen; Ma, Jie; Sheng, Li; Zhang, Dongming; Chen, Xiaoguang; Yang, Jingzhi; Wang, Dongjie (Frontiers in Pharmacology, 2017)
Background Septic acute kidney injury (AKI) causes high mortality in critical care units, and no effective therapy exists in clinical treatment. In the current study, water and ethanol extracts of Hydrangea paniculata (HP), a traditional Chinese medicinal plant, were used to test its renoprotective effects in a lipopolysaccharide (LPS)-induced murine model of septic AKI. Methods C57BL/6 mice were orally pretreated with HP three times, and then intraperitoneal LPS injection was used to induce septic AKI. Blood from animals was collected for biochemical analysis and kidneys were obtained for pathological analysis. Kidney tissue homogenates were used to investigate the effect of HP on inflammation and oxidative stress. Immunohistochemistry was used to investigate tubular cell apoptosis. Flow cytometry was conducted to analyze leukocyte infiltration into the kidneys. Blood cell counts were used to analyze changes in peripheral leukocytes. In vitro studies with Ana1 and HK-2 cells stimulated by LPS were used to investigate the anti-inflammatory effects and inhibition of signaling pathways by HP. Results HP significantly decreased blood urea nitrogen and plasma neutrophil gelatinase-associated lipocalin concentrations, as well as tubulointerstitium injuries in septic AKI mice. Moreover, HP administration improved animal survival following lethal LPS injections. HP ameliorated apoptosis of tubular cells by inhibiting the cleavage of caspase 3 and caspase 7. HP also showed pronounced antioxidant activity in AKI kidneys. HP showed anti-inflammatory effects by inhibiting the infiltration of neutrophils and macrophages into kidney tissues induced by LPS, as well as inhibiting the production of cytokines and chemokines. Possible molecular mechanisms included HP inhibition of NF-κB nuclear translocation in LPS-induced macrophages and tubular cells, and reduction of STAT3, STAT1, and ERK1/2 phosphorylation stimulated by LPS in vitro. Single acute toxicity tests confirmed that HP, even at 5 g/kg dosage, does not cause animal death. Pharmacokinetics also showed that coumarins from HP could be metabolized into two bioactive compounds, umbelliferone and esculetin. Conclusions HP extract may protect renal function in LPS-induced AKI by anti-inflammatory and antioxidant activities, and has potential in the critical care of AKI.